Development of intra- and interspecies somatic cell nuclear transfer protocols using ear fibroblast cells as donor karyoplasts for production of cloned caprine embryos / Kwong Phek Jin - Kwong, Phek Jin (2012)
In Malaysia, the application of various assisted reproductive technologies (ART), particularly reproductive cloning, in goat production system, is still at the infancy stage. Thus, this pioneering study was conducted with the aim to produce cloned caprine embryos through intraspecies somatic cell nuclear transfer (intraspSCNT) and interspecies somatic cell nuclear transfer (interspSCNT) techniques using caprine ear skin fibroblast cell as donor karyoplast as well as developing a protocol for caprine SCNT (intraspSCNT and interspSCNT). The caprine intraspSCNT and interspSCNT (caprine karyoplast-bovine cytoplast) studies were carried out using caprine and bovine oocytes obtained from the abattoir-derived ovaries or via laparoscopic ovum pick-up (LOPU) technique on superstimulated does. The collected oocytes were subsequently cultured in in vitro maturation (IVM) medium according to the optimised duration. The matured oocytes were then subjected to enucleation process. This was followed by the transfer of caprine ear skin fibroblast cell into the enucleated oocytes. The couplets were electrofused and chemically activated before in vitro cultured in CO2 (5%) incubator at 38.5°C in humidified atmosphere for 8 days. The cloned blastocyst was stained with Hoechst 33342 dye for blastomere enumeration. The data were presented as mean±SEM and were analysed using one-way ANOVA. The significant differences among treatments were further analysed by DMRT and P<0.05 was considered significant. In Experiment 1, the effect of different sources of gonadotrophin (PMSG versus pFSH) on caprine superstimulatory responses was evaluated. Both PMSG and pFSH employed in the designated regimes have relatively similar potential to stimulate caprine ovaries for oocyte retrieval via LOPU with the average oocyte yield of 11 and 12 oocytes per doe, respectively. However, the efficacy of PMSG could not surpass the pFSH, particularly when it was employed in the repeated ovarian stimulation and oocyte iv retrieval protocols. This was indicated by the lower number of oocyte yielded from PMSG treated group than pFSH (P<0.05) group at the third OR cycle. In Experiment 2, the effect of different sources of caprine oocytes (LOPU- versus abattoir-derived ovaries) on the oocyte yield, grades and maturation performance was investigated. Oocyte retrieval from LOPU source produced better quality oocytes (Grades A and B) (39 to 40%) compared to abattoir source (18 to 32%), even though the oocyte yield was lower in LOPU. Correspondingly, caprine oocytes from LOPU gave higher maturation rate than abattoir-derived ovaries (79.6% versus 69.7%, respectively) when the optimised IVM duration was used. The optimum IVM durations for caprine oocytes retrieved from LOPU- and abattoir derived-ovaries determined in this laboratory setting were 18 to 22 hours and 22 to 26 hours, respectively. In Experiment 3, production of cloned bovine and gaur embryos via intraspSCNT and interspSCNT approaches was carried out as a preliminary study for caprine SCNT research. Both cloned bovine and gaur embryos could be produced in vitro up to hatched blastocyst stage with no significant difference (P>0.05) in their developmental rate (18.6% and 19%, respectively). In Experiment 4, improvement on the in vitro cloned caprine embryos production by considering the effects of maturation duration, activation treatment and in vitro culture protocol was carried out. Caprine oocytes from superstimulated does which was matured at 18 to 22 hours gave a significantly (P<0.05) higher maturation rate, enucleation rate and IVD rates (2-cell to morula stage) than oocytes which was matured at 23 to 27 hours after intraspSCNT. Both activation protocols [(7% EtOH + CD-CHX) and (CaI + 6-DMAP)] had comparable efficiency in inducing the development of caprine reconstructed embryos. KSOMaa basal medium supported the in vitro development of cloned caprine embryos better than mSOFaa in the one-step culture system as cloned blastocyst could only be developed when cultured in KSOMaa as in v this study. Increasing glucose supplementation to 2.78 mM in KSOMaa medium at Day 2 of in vitro culture (IVC) enhanced the cloned caprine blastocyst rate (19.9%) and promoted hatching of blastocyst (15.6%). In Experiment 5, the efficacy of producing cloned caprine embryos using intraspecies SCNT (intraspSCNT) versus interspecies SCNT (interspSCNT) approaches was evaluated. Both intraspSCNT and interspSCNT approaches enabled production of cloned caprine blastocyst with the rate of 17.3% and 8.3%, respectively. However, the efficiency of interspSCNT approach was still low compared to the intraspSCNT approach. No pregnancy was detected after the attempt of embryo transfer on the cloned caprine embryos. In a nutshell, the present study resulted in several novel findings in Malaysia animal reproduction research scenario. This includes the success in producing cloned caprine embryos up to hatched blastocyst stage through intraspSCNT and interspSCNT (caprine karyoplast-bovine cytoplast) approaches using caprine ear skin fibroblast cell; the discovery of a new IVC system that could support the caprine embryos in vitro development to blastocyst stage (using KSOMaa at Day 0 to Day 2 and increasing the glucose supplementation to 2.78 mM in KSOMaa for Day 2 to Day 8 of in vitro culture); protocols for caprine intraspSCNT and interspSCNT were developed and could be served as references for future studies related to goat somatic cell nuclear transfer in this laboratory.